2020
DOI: 10.1371/journal.pone.0230819
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel regulators of STAT3 activity

Abstract: STAT3 mediates signalling downstream of cytokine and growth factor receptors where it acts as a transcription factor for its target genes, including oncogenes and cell survival regulating genes. STAT3 has been found to be persistently activated in many types of cancers, primarily through its tyrosine phosphorylation (Y705). Here, we show that constitutive STAT3 activation protects cells from cytotoxic drug responses of several drug classes. To find novel and potentially targetable STAT3 regulators we performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…It is required for progression through the G1 phase of the cell cycle and protects cells from UV-induced apoptosis. Mutations in the contact region of STAT3 both reduce c-Jun–STAT3 protein interaction and disrupt the cooperation between these two proteins, which is required for maximal IL-6-dependent gene activation driven by the α2-macroglobulin enhancer [ 61 , 63 ]. c-Fos encodes a 62 kDa protein, which forms a heterodimer with c-Jun, resulting in the formation of the AP-1 (activator protein-1) complex, which binds DNA at AP-1 specific sites.…”
Section: Role Of Stat3 In Oncogenic Transformationmentioning
confidence: 99%
“…It is required for progression through the G1 phase of the cell cycle and protects cells from UV-induced apoptosis. Mutations in the contact region of STAT3 both reduce c-Jun–STAT3 protein interaction and disrupt the cooperation between these two proteins, which is required for maximal IL-6-dependent gene activation driven by the α2-macroglobulin enhancer [ 61 , 63 ]. c-Fos encodes a 62 kDa protein, which forms a heterodimer with c-Jun, resulting in the formation of the AP-1 (activator protein-1) complex, which binds DNA at AP-1 specific sites.…”
Section: Role Of Stat3 In Oncogenic Transformationmentioning
confidence: 99%
“…Indeed, we previously found that JAK2 mRNA is m 6 A-modified during the type I IFN response [5]. However, as FTO depletion may regulate the expression of multiple kinases or phosphatases that control STAT3 phosphorylation [47], additional targeted studies will be required for a more complete understanding of the mechanisms by which FTO regulates STAT3 activation.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest a role for PTPRH in differentiation programs limiting neuroblastoma cell growth, and are consistent with the upregulation of PTPRH expression upon differentiation of other cell types ( Nunes-Xavier et al, 2012 ; Nunes-Xavier et al, 2013 ), as well as with its downregulation in some cancer types ( Nagano et al, 2003 ; Bujko et al, 2017 ). Remarkably, PTPRH was selected in a siRNA screening as a potential STAT3 regulator ( Parri et al, 2020 ), and it has also been found to associate with and dephosphorylate several RTK, including EGFR and IR ( Shintani et al, 2015 ; Yao et al, 2017 ). Since the related PTPRO enzyme, which is mainly expressed in the developing nervous system, dephosphorylates Trk receptors ( Hower et al, 2009 ; Gatto et al, 2013 ), a role is possible for PTPRH in the direct regulation of Trk signaling in neuroblastoma cells.…”
Section: Classical Protein Tyrosine Phosphatases In Neuroblastomamentioning
confidence: 99%